Implementation of virtual environment using VIRTOOLS - Balbed M.A.M.; Ibrahim N.; Yusof A.M. (2023)
VRML is one of the most common and popular virtual reality development tools available in the market. This low end product is widely used in school or college. High end product such as Sense8, EON, Cartia and many others have been in the market for quite number of years. These applications have been popularly used in the big industries such as medical, automobile and infrastructure design. However, for our purpose of environment visualization and immersion, Virtools development kit was used. The main focus of this paper is to describe the approach used in producing an immersive and interactive 3D environment used to treat acrophobia. The 3D environment consists of a busy city surrounded by tall buildings. The advantages and benefit of using Virtools as virtual reality development tool is then explained. 2008 IEEE.